European Dermatology Forum guidelines on topical photodynamic therapy 2019 Part 1: treatment delivery and established indications – actinic keratoses, Bowen's disease and basal cell carcinomas. (28th November 2019) - Morton, C.A.; Szeimies, R.‐M.; Basset‐Seguin, N.; Calzavara‐Pinton, P.; Gilaberte, Y.; Hædersdal, M.; Hofbauer, G.F.L.; Hunger, R.E.; Karrer, S.; Piaserico, S.; Ulrich, C.; Wennberg, A.‐M.; et al.
Abstract: Topical photodynamic therapy (PDT) is a widely approved therapy for actinic keratoses, Bowen's disease (squamous cell carcinoma in situ ), superficial and certain thin basal cell carcinomas. Recurrence rates when standard treatment protocols are used are typically equivalent to existing therapies, although inferior to surgery for nodular basal cell carcinoma. PDT can be used both as lesional and field therapies and has the potential to delay/reduce the development of new lesions. A protocol using daylight to treat actinic keratoses is widely practised, with conventional PDT using a red light after typically a 3‐h period of occlusion employed for other superficial skin cancer indications as well as for actinic keratoses when daylight therapy is not feasible. PDT is a well‐tolerated therapy although discomfort associated with conventional protocol may require pain‐reduction measures. PDT using daylight is associated with no or minimal pain and preferred by patient. There is an emerging literature on enhancing conventional PDT protocols or combined PDT with another treatment to increase response rates. This guideline, published over two parts, considers all current approved and emerging indications for the use of topical PDT in dermatology, prepared by the PDT subgroup of the European Dermatology Forum guidelines committee. It presents consensual expert recommendations reflecting current published evidence.